Alteraciones del Yo en las fases iniciales del espectro esquizofrénico - Valle, Rubén (2019)
ABSTRACT The pathogenic nucleus of schizophrenia has varied according to the different eras and influences of distinguished clinical researchers. Self-disorders have also been recognised to be at the heart of this disorder, although they have seldom been studied due to their subjective nature. Recently, due to the growing interest in the study of the early stages of schizophrenia, the study of self-disorders has been resumed. The self-disorders in schizophrenia model, developed by Sass and Parnas, proposes that in this disorder the person suffers loss of the first-person perspective and experiences hyperreflexibility, diminished self-affection and disturbance of the field of awareness. Therefore, the person experiences feelings of strangeness about him/herself, difficulty in understanding the common sense of things and difficulty interacting with his/her environment. Based on this model, self-disorder evaluation instruments have been developed and empirical studies have been conducted to evaluate people at risk of developing a schizophrenia spectrum disorder. These studies show that self-disorders are found in prepsychotic stages and that their manifestation may predict the transition to schizophrenia spectrum disorders. These results have important clinical implications as they enable people in the early stages of the disorder to be identified and create the opportunity to apply early therapeutic interventions.